PENGARUH PEMBERIAN ANTIKOAGULAN TERHADAP KEMAMPUAN REPRODUKSI NYAMUK Aedes aegypti DI LABORATORIUM - , NOVYAN LUSIYANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The mosquito Aedes aegypti can be bred in the laboratory. Blood feeding aims to provide adult mosquitoes feed on blood through a membrane feeding using Artificial Membrane Feeding (AMF) were given blood with anticoagulant. Anticoagulants are expected to decrease the reproductive capacity of Ae. aegypti in the laboratory . Objective: To determine the effect of anticoagulant K3EDTA, heparin and Na.citrat on mosquito reproduction capabilities that include feeding rate, fecundity, hatchability, pre adult development and survival rate of Ae. aegypti in the laboratory . Materials and Methods: Seven hundred and twenty two Ae. aegypti mosquitoes were divided into 4 groups. Ae. agypti mosquitoes each group was weighted before and after blood feeding to calculate the abiliti to suck blood. Group II, III, IV were fed blood that containing K3EDTA, heparin and Na.citrat anticoagulant through artificial membrane feeding, while the first group was administered with direct fed of human blood as a control group. Mosquitoes subject recently maintained in individualy for a week in papper cup for oviposisi. Eggs were calculated and hatched on the other papper cup to be seen the hatchability and pre adult development. Survival rate of mosquito had been seen in 30 days after blood feeding . The resulting data were analyzed by ANOVA test . Results: The feeding rate and fecundity of Ae. aegypti in the heparin group (1.84 mg, 53.28 grains/mosquitoes) is better than the group K3EDTA (1.57 mg, 46.94 grains/tail) and Na.citrat (1.72 mg, 49.9 grains/mosquitoes). Hatchability K3EDTA group (99.88 %) better than the control group (99.49 %), heparin (99.33